Albumin as a versatile platform for drug half-life extension - Sleep, Darrell; Cameron, Jason; Evans, Leslie R. (Biochimica et biophysica acta, 2013)
Albumin is the most abundant plasma protein, is highly soluble, very stable and has an extraordinarily long circulatory half-life as a direct result of its size and interaction with the FcRn mediated recycling pathway. In contrast, many therapeutic molecules are smaller than the renal filtration threshold and are rapidly lost from the circulation thereby limiting their therapeutic potential. Albumin can be used in a variety of ways to increase the circulatory half-life of such molecules. This article will review the mechanisms which underpin albumin's extraordinarily long circulatory half-life and how the understanding of these processes are currently being employed to extend the circulatory half-life of drugs which can be engineered to bind to albumin, or are conjugated to, or genetically fused to, albumin. The recent and growing understanding of the pivotal role of FcRn in maintaining the extended circulatory half-life of albumin will necessitate a greater and more thorough investigation of suitable pre-clinical model systems for assessing the pharmacokinetic profiles of drugs associated, conjugated or fused to albumin. Association, conjugation or fusion of therapeutic drugs to albumin is a well-accepted and established half-life extension technology. The manipulation of the albumin–FcRn interaction will facilitate the modulation of the circulatory half-life of albumin-enabled drugs, leading to superior pharmacokinetics tailored to the disease state and increased patient compliance. This article is part of a Special Issue entitled Serum Albumin. •Albumin has an extraordinarily long circulatory half-life.•Albumin's half-life results from its size and interaction with an FcRn mediated recycling pathway.•Albumin is used to extend the circulatory half-life of drugs.•Drugs can be engineered to bind to albumin, are conjugated to or are genetically fused to albumin.•This review will focus on peptide and protein half-life extension through albumin interaction.